Descentralização e corrupção: indícios e evidências a partir das constatações de auditoria nos municípios brasileiros - Vieira, Michelle Aparecida (2022)
Decentralization has been encouraged in various countries, on the grounds that the devolution of powers and responsibilities to local governments tends to increase the efficiency of the public sector and promote greater accountability. However, recent experiences have highlighted several problems linked to the transfer of authority to local governments, of which the abuse of power has culminated in acts of corruption. On this question, the Second Generation Fiscal Federalism literature suggests that there are incentives linked to the government's fiscal structure that can lead to different results that, most of the time, are contrary to the public interest. In this perspective, Public Choice Theory (PCT) and New Institutional Economy (NIE) have offered important contributions for the strengthening of this theoretical field. According to PCT, the fiscal structures create incentives for public decision makers, who, being selfish and rational, tend to act in their own interest. For this, it is necessary to design a fiscal structure that incorporates a set of restrictions that limit the power of two political agents. In contrast, NIE contributed to this field by assuming that the incentives that influence these decisions, which are already present in the fiscal structure of the federal entity, can be altered in the presence of institutions that subordinate officials to acting in the public interest. In this sense, this study had the objective of verifying the effect of fiscal decentralization on the indications of corruption evidenced by Brazilian municipalities. It is assumed that this relationship, positive or negative, is influenced by the incentives present in the fiscal structure of the government and the current governance structure in the manager's decision environment, and that these conditions vary when considering the existing socioeconomic differences in the Brazilian federation. Adopting as a proxy for municipal corruption an indicator constructed from the evidence presented by the auditors of the Controllership Geral da União (CGU), not under the Public Sorteios Audit Program, this study found that: i) corruption reduced to the extent that municipalities use resources from the exercise of their tax jurisdiction; ii) fiscal decentralization increases corruption when exercised through the transfer of resources, as with the FPM; iii) that the direct linking of some resources received, such as Fundeb, seeks to restrict or increase inefficient public spending, tends to contribute to the emergence of corruption, through the inefficient use of public resources and iv) that these results are conditioned existence of a local governance structure.